Evaluation of an educational intervention on COVID-19 and responsible pet ownership among employees of a private company in Lima, Peru, 2021 - Sandoval Noriega, Mercedes (2025)
The objective of the study was to evaluate the impact of an educational intervention on knowledge of COVID-19 and responsible pet ownership among employees of a private telecommunications company in Lima, Peru, during the period from May to November 2021. Thirty participants were evaluated at three key moments: before the intervention, immediately after, and six months after its implementation. The intervention consisted of five educational sessions, each lasting 40 to 50 minutes, covering topics such as COVID-19, its relationship with companion animals, the consequences of misinformation, and the importance of responsible pet ownership. Initial knowledge about COVID-19 and companion animals was 70.0%, and it reached 100% immediately after the intervention and the six-month follow-up. On the other hand, responsible pet ownership increased from 60.0%, before the intervention, to 86.7% six months later. The educational intervention showed a positive and significant effect (p < 0.05) on improving responsible pet ownership practices.